2008
DOI: 10.1007/s10758-008-9127-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational Construction as a Means to Coordinate Representations of Infinity

Abstract: In this paper, we describe a design experiment aimed at helping students to explore and develop concepts of infinite processes and objects. Our approach is based on the design and development of a computational microworld, which afforded students the means to construct a range of representational models (symbolic, visual and numeric) of infinity-related objects (infinite sequences, in particular). We present episodes based on four students' activities, seeking to illustrate how the available tools mediated stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…From this contemporary hermeneutic viewpoint, mathematical thinking emerges from a process of interpretation, with understanding and concepts perceived as temporary fixes of ongoing development, rather than permanent realities. This resonates with the notion of the hermeneutic circle, with learning and understanding always in transition (Ricoeur, 1981). Our understanding of mathematical ideas emerges through cyclical engagements with the phenomena and the continual drawing forward of previous encounters and understandings.…”
Section: Methodsmentioning
confidence: 68%
“…From this contemporary hermeneutic viewpoint, mathematical thinking emerges from a process of interpretation, with understanding and concepts perceived as temporary fixes of ongoing development, rather than permanent realities. This resonates with the notion of the hermeneutic circle, with learning and understanding always in transition (Ricoeur, 1981). Our understanding of mathematical ideas emerges through cyclical engagements with the phenomena and the continual drawing forward of previous encounters and understandings.…”
Section: Methodsmentioning
confidence: 68%
“…Several studies focus on the various integrations of technologies into current educational settings and some on the future potentials of new emerging technologies [4]. These experiences have deepened students' understanding and boosted their Sustainability 2022, 14, 7237 2 of 15 confidence and enjoyment of engaging with mathematics and other science subjects [5][6][7][8][9]. Increasing students' confidence and enjoyment in engaging with mathematics and other science subjects should contribute to sustainable learning, according to [10].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond translating, some mathematics educators have already mentioned the need to make the connections between representations more explicit (Duval, 2006;Kaput, 1989;Marshall et al, 2010;Prediger & Wessel, 2013;Sacristán & Noss, 2008). The teaching practice is therefore now often referred to as connecting multiple representations: for example, the practical paper by Marshall et al (2010) suggested the instructional strategy that teachers engage students in dialog to make explicit the connections among representations (similarly NCTM, 2014).…”
Section: Connecting Rather Than Translating As a Relevant Student Pro...mentioning
confidence: 99%